Immediate early protein of equid herpesvirus type 1 as a target for cytotoxic T-lymphocytes in the thoroughbred horse - Kydd, Julia H.; Case, Ruth; Minke, Julius; Audonnet, Jean-Christophe; Wagner, Bettina; Antczak, Douglas F. (Microbiology Society, 2014)
Cytotoxic T-lymphocytes (CTLs) are associated with protective immunity against disease caused by equid herpesvirus type 1 (EHV-1). However, the EHV-1 target proteins for CTLs are poorly defined. This limits the development of vaccine candidates designed to stimulate strong CTL immunity. Here, classical CTL assays using lymphocytes from horses of three defined MHC class I types that experienced natural infection with EHV-1 and a modified vaccinia virus construct containing an EHV-1 gene encoding the immediate-early (IE) protein are reported. Horses homozygous for the equine leukocyte antigen (ELA)-A2 haplotype, but not the ELA-A5 haplotype, produced MHC-restricted CTL responses against the IE protein. Previously, horses homozygous for the ELA-A3 haplotype also mounted CTL responses against the IE protein. Both haplotypes are common in major horse breeds, including the Thoroughbred. Thus, the IE protein is an attractive candidate molecule for future studies of T-cell immunity to EHV-1 in the horse.